Antimicrobial activity and Phytochemical Constituents of Edible Mushrooms Pleurotus ostreatus and Agaricus bisporus Sold in Enugu Metropolis - Nwobodo, David; Anoruo, Philadelphia; Ojukwu , Ihuoma; Egwuatu, Pius (Journal of Current Biomedical Research, 2021)
The continuous rise in antimicrobial resistance has led to an unending search for newer, cheaper, and safer sources of antimicrobials. Mushrooms are known to possess bioactive metabolites, which can serve as pharmaceutical agents. The antimicrobial activity of aqueous and methanol extracts from edible mushrooms Pleurotus ostreatus and Agaricus bisporus against four pathogenic bacterial strains; Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa, and the yeast Candida albicans were evaluated using the agar well diffusion method. Preliminary phytochemical screening of the mushroom Pleurotus ostreatus and Agaricus bisporus extracts revealed the presence of some essential phytochemicals which include; alkaloids, glycoside and saponins. The best antibacterial activity was displayed by the methanol extract of Pleurotus ostreatus against Bacillus subtilis (IZD=8.00 ± 1.40 mm) and Staphylococcus aureus (6.0 ± 0.11 mm) at a concentration of 50mg/ml, whereas aqueous extract showed comparatively lesser activity. None of the extracts displayed any antifungal activity in this study. The methanol extracts of Pluerotus ostreatus may contain bioactive compounds which also serve as potential antibacterial agents for the treatment of infections caused by Bacillus subtilis.